2020
DOI: 10.1039/d0cp01860k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of a Janus SnSSe monolayer: effects of strain and electric field

Abstract: In this paper, detailed investigations of the electronic and optical properties of a Janus SnSSe monolayer under a biaxial strain and electric field using ab initio methods are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 37 publications
7
32
0
Order By: Relevance
“…1,2 To serve a variety of purposes, scientists have sought to alter their physical and chemical properties. In addition to traditional methods such as the applications of deformation or electric eld, 3,4 placing on semiconductor substrates or the creation of heterostructures, 5,6 recently, surface functionalization has emerged as one of the effective ways to alter the physical properties of 2D materials. 7,8 Physical properties of surface-functionalized 2D monolayers have been calculated using many different methods.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To serve a variety of purposes, scientists have sought to alter their physical and chemical properties. In addition to traditional methods such as the applications of deformation or electric eld, 3,4 placing on semiconductor substrates or the creation of heterostructures, 5,6 recently, surface functionalization has emerged as one of the effective ways to alter the physical properties of 2D materials. 7,8 Physical properties of surface-functionalized 2D monolayers have been calculated using many different methods.…”
Section: Introductionmentioning
confidence: 99%
“…Using first-principles calculations, Yuan et al [ 20 ] found that the formation energies of Janus MnSTe, MnSeTe, MnSSe, and VSeTe can be comparable to those of the parents MnS 2 , MnSe 2 , MnTe 2 , VSe 2 , and VTe 2 . In addition, previous ab-initio studies confirmed the chemical, dynamical, and mechanical stability of Janus monolayer SnSSe, which exhibits promising optoelectronic properties for solar cells applications and can be also used as appealing industrial waste thermoelectric materials [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 92%
“…Although many Janus monolayers have been proposed to be energetically and dynamically stable in recent years [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], less is known about their thermal stability and an explicit understanding is therefore quite necessary, especially considering various application potentials at different temperature regions. In this work, using the Janus monolayers SnXY (X, Y = O, S, Se) as a prototypical class of examples, we focus on their thermal stability by performing ab-initio molecular dynamics (AIMD) simulations at a series of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic and optical properties of Janus monolayer MoSSe are investigated in Do et al (2021) by doping of Ce and La. Impacts of electric field and strain on optical and electronic properties of the Janus monolayer Ga 2 SeTe, Ga 2 STe, SnSSe and Al 2 SSe were reported in Vu et al (2020); Nguyen et al 2020a;Nguyen et al 2020b;Nhan et al 2020). In (Cui et al 2020) the heterostructures of Janus MoSSe and ZnO are investigated.…”
Section: Introductionmentioning
confidence: 99%